Ultrastructural Alterations Associated with the Growth of Resistant Pseudomonas aeruginosa in the Presence of Benzalkonium Chloride - Hoffmann, Hans-Peter (1973)
Cells of Pseudomonas aeruginosa resistant to benzalkonium chloride (BC) underwent unique ultrastructural reorganizations when they were grown in the presence of 1 mg of BC/ml. The resistant cells usually contained a single, centrally positioned pseudovacuole. The pseudovacuole was surrounded by a diffuse substance that spread irregularly throughout the cytoplasm. The presence of the pseudovacuole seemed to cause a physical compartmentalization of the cytoplasm into random pockets of ribosomes and nuclear material. Contained within the pseudovacuole was a horseshoe-shaped, electron-dense body which was bounded by a trilaminar membrane 5.2 nm in width. These bodies averaged 77 nm when measured through the long axis. The surfaces of resistant cells were covered by an additional layer not found in sensitive cells. Thin sections of sensitive cells which had been treated with 1 mg of BC/ml showed little or no lysis. The cytoplasm appeared to be deeply stained and coagulated. Ribosomes were no longer distinctly visible. Although the cell wall remained intact, the cell membrane was dissolved and fragmented. BC-grown resistant cells could not be successfully stained by standard techniques; however, details were demonstrated with the aid of a combination of 1.5% glutaraldehyde, 1% osmium tetroxide, and 1% phosphotungstic acid prepared in 0.1 m sodium dimethylarsonate buffer (pH 6.8).